1999
DOI: 10.1111/j.1600-0447.1999.tb10911.x
|View full text |Cite
|
Sign up to set email alerts
|

Bulimia and bulimic behaviour in middle adolescence: more common than thought?

Abstract: Bulimia and bulimic eating behaviour appear to be more common than was previously thought in middle adolescence, and also among boys. Bulimia deserves more attention in younger age groups than main risk groups so far considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 30 publications
4
38
1
1
Order By: Relevance
“…In black and white women with binge eating disorder, physical abuse at all severity levels was significantly more common than in the matched healthy comparison groups. Moreover, having been bullied by peers was associated significantly with binge eating disorder in both ethnic groups, consistent with the results of a survey of secondary school students (21) that found that binge eating was associated with bullying by peers. In both ethnic groups, childhood physical abuse and bullying by peers were found to be associated with general risk for the development of mental disorders rather than representing unique risk factors for the development of binge eating disorder.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In black and white women with binge eating disorder, physical abuse at all severity levels was significantly more common than in the matched healthy comparison groups. Moreover, having been bullied by peers was associated significantly with binge eating disorder in both ethnic groups, consistent with the results of a survey of secondary school students (21) that found that binge eating was associated with bullying by peers. In both ethnic groups, childhood physical abuse and bullying by peers were found to be associated with general risk for the development of mental disorders rather than representing unique risk factors for the development of binge eating disorder.…”
Section: Discussionsupporting
confidence: 78%
“…Research on the adverse mental health effects of childhood physical abuse has underscored its public health importance (18,19). Physical bullying by peers is another form of abuse that is gaining attention, given data documenting its relationship to adverse mental health outcomes (20), including binge eating (21). Finally, studies of health and psychological problems among black Americans have identified discrimination based on ethnicity as an important ethnicity-specific risk factor (22,23).…”
Section: (Am J Psychiatry 2002; 159:1902-1907)mentioning
confidence: 99%
“…Weight teasing history was a unique predictor of drive for thinness, even when assessed alongside other predictors: frequency of appearance comparison and internalization of societal values of thinness (Stormer & Thompson, 1996). In a Finnish study of nearly 9,000 adolescents (14 -16 years old), girls who had been bullied at school at least weekly were over twice as likely, and bullied boys were 10 times as likely, to meet criteria for bulimia (Kaltiala-Heino, Rissanen, Rimpela, & Rantanen, 1999). Adolescents with bulimia also had a higher BMI than did those without bulimia, though the correlation between weight and bullying was not examined in this investigation.…”
Section: Physical Health Consequencesmentioning
confidence: 99%
“…In particular, studies indicate that bullying experiences are associated with disordered eating, namely among adolescent girls (Engström & Norring, 2002;Gilbert, 2002;Gilbert & Thompson, 2002;Kaltiala-Heino, Rissanen, Rimpela, & Rantanen, 1999;Menzel et al, 2010). Also, there is evidence suggesting that bullying is associated with adolescents' negative perceptions that their body is the target of criticism from others (Lunde, Frisén, & Hwang, 2006).…”
Section: Introductionmentioning
confidence: 99%